2022
DOI: 10.1371/journal.pone.0264417
|View full text |Cite
|
Sign up to set email alerts
|

Health facility readiness to provide integrated Family Planning, Maternal and Child Health (FPMCH) services in Nepal: Evidence from the comprehensive health facility survey

Abstract: Introduction This study aimed to build the emergent body of evidence of family planning and maternal and child health (FPMCH) service integration benefits that can be useful in reaching the target of sustainable development goals (SDGs). Methods We utilized data from the 2015 Nepal Health Facility Survey and used the World Health Organization service readiness manual for defining the service readiness indicator score of all services related to FPMCH integration. Composite readiness index for all services inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Nutrition-sensitive interventions targeting underlying determinants of malnutrition, such as poverty, integrating nutrition counseling into maternal and child health and family planning programs, and evaluating the cost-effectiveness of social safety net programs are crucial [62,75,76,82,88]. The study emphasized that despite successful progress in improving average nutritional status, pro-poor aspects of nutritional transition need more attention for child stunting [9,32,33,89].…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition-sensitive interventions targeting underlying determinants of malnutrition, such as poverty, integrating nutrition counseling into maternal and child health and family planning programs, and evaluating the cost-effectiveness of social safety net programs are crucial [62,75,76,82,88]. The study emphasized that despite successful progress in improving average nutritional status, pro-poor aspects of nutritional transition need more attention for child stunting [9,32,33,89].…”
Section: Discussionmentioning
confidence: 99%
“…To increase the agglomeration of healthcare resources, the government should consider the negative effect of MMR in one province and a spatial spillover effect in its adjacent provinces. For example, the government can place a high priority on maternal and child health (MCH) services and integrate vertical programs (e.g., family planning) related to MCH and alleviate the medical burden of individual residents ( 39 ). In addition, considering the positive spillover effect of MMR on the agglomeration of the beds and health workforce, the government should also construct and strengthen interprovincial cooperation in health planning and jointly formulate health development strategies to reduce MMR.…”
Section: Discussionmentioning
confidence: 99%
“…This infers that the services are designed to respond to the needs of the women and that their preferences are considered as important. A study done in Nepal found that increase in external supervision would increase the facility scores for facility readiness for family planning integration in maternal, and child health care [ 54 ]. However, our study did not assess the frequency of supervision of the midwives within the study area.…”
Section: Discussionmentioning
confidence: 99%